Left Behind by COVID-19: Experiences of "Left-Behind" Girls in Rural China. Issue 3 (1st December 2020) - Wang, Jue
Abstract: "Left-behind" children in rural China are those whose parents seek work in urban areas and leave them behind in their hometowns. In this article, I focus on the experiences of five young "left-behind" girls who were socially isolated because of the COVID-19 pandemic. Based on the Chinese authorities' instruction to schools to "Stop classes, but don't stop learning, " I examine micro-level data on the tensions and challenges experienced by these girls during the COVID-19 lockdown. I look at how the pandemic has affected these girls in relation to school and family life and suggest that it has exposed and magnified gender inequalities, particularly those related to the maltreatment exerted by their guardians and/or brothers, that have left them even further behind.